Cannabis-induced altered states of consciousness are associated with specific dynamic brain connectivity states - Zaytseva, Yuliya; Horáček, Jiří; Hlinka, Jaroslav; Fajnerová, Iveta; Androvičová, Renata; Tintěra, Jaroslav; Salvi, Virginio; Balíková, Marie; Hložek, Tomáš; Španiel, Filip; Páleníček, Tomáš (Journal of psychopharmacology (Oxford), 2019)
Cannabis, and specifically one of its active compounds delta-9-tetrahydrocannabinol in recreational doses, has a variety of effects on cognitive processes. Most studies employ resting state functional magnetic resonance imaging techniques to assess the stationary effects of cannabis and to-date one report addressed the impact of delta-9-tetrahydrocannabinol on the dynamics of whole-brain functional connectivity. Using a repeated-measures, within-subjects design, 19 healthy occasional cannabis users (smoking cannabis ⩽2 per week) underwent resting state functional magnetic resonance imaging scans. Each subject underwent two scans: in the intoxicated condition, shortly after smoking a cannabis cigarette, and in the non-intoxicated condition, with the subject being free from cannabinoids for at least one week before. All sessions were randomized and performed in a four-week interval. Data were analysed employing a standard independent component analysis approach with subsequent tracking of the functional connectivity dynamics, which allowed six connectivity clusters (states) to be individuated. Using standard independent component analysis in resting state functional connectivity, a group effect was found in the precuneus connectivity. With a dynamic independent component analysis approach, we identified one transient connectivity state, characterized by high connectivity within and between auditory and somato-motor cortices and anti-correlation with subcortical structures and the cerebellum that was only found during the intoxicated condition. Behavioural measures of the subjective experiences of changed perceptions and tetrahydrocannabinol plasma levels during intoxication were associated with this state. With the help of the dynamic connectivity approach we could elucidate neural correlates of the transitory perceptual changes induced by delta-9-tetrahydrocannabinol in cannabis users, and possibly identify a biomarker of cannabis intoxication.